Import Clearance Planning Study at Tanjung Priok Port - Jakarta - Harry Purwoko; Alya Maulina (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The objective of this journal writing is to see the gap between SPPB (Surat Persetujuan Pengeluaran Barang or Import Customs Approval) preparation planning, SPPB respond, and container delivery to importer’s premises that take place at OKATRANS (the brand of PT Olak Kemang), and what are the proposed action plans to increase customer satisfaction in term of right time container delivery, minimizing logistics cost, and improving dwelling time. The research method used here is combining quantitative and qualitative description method.